1990
DOI: 10.1111/j.1365-2621.1990.tb01585.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Lactic Acid Bacteria during Spray Drying of Plain Yogurt

Abstract: Survival of Streptococcus salivatius subsp. thermophilus and Lactobacillus debnceckii subsp. bulgariclcs was determined under various processing conditions for spray drying. Numbers of both microorganisms decreased with increased outlet or inlet air temperature, and atomizing air pressure. Outlet air temperature was a major parameter affectingnumber of survivors. Suitable-conditions were inlet air 160°C outlet air 60°C. atomizinz air nressure 98 kPa. hot air flow 0.28 m3/ min, and feed temperatuG 3tiC. Spray-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 6 publications
6
39
1
Order By: Relevance
“…The probiotic survival rate decreased during spray drying as the outlet temperature increased for both NFBC 338 (r ϭ Ϫ0.93) and UCC 118 (r ϭ Ϫ0.91) ( Fig. 2A and 3A), as previously observed in studies performed with other microorganisms (8,16,18). The survival rates for L. paracasei NFBC 338 during spray drying ranged from 97% at an outlet temperature of 70 to 75°C to 0% at 120°C (Fig.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The probiotic survival rate decreased during spray drying as the outlet temperature increased for both NFBC 338 (r ϭ Ϫ0.93) and UCC 118 (r ϭ Ϫ0.91) ( Fig. 2A and 3A), as previously observed in studies performed with other microorganisms (8,16,18). The survival rates for L. paracasei NFBC 338 during spray drying ranged from 97% at an outlet temperature of 70 to 75°C to 0% at 120°C (Fig.…”
Section: Resultssupporting
confidence: 68%
“…In previous studies, workers have investigated the use of spray drying as a way to preserve yogurt with viable microorganisms (18) and dairy starter cultures, such as Lactobacillus bulgaricus and Streptococcus thermophilus (23,33,34), and as a way to attenuate adjunct cultures, such as Lactobacillus helveticus (16,17). In addition to maintaining the viability of probiotic cultures, it is important that probiotic properties are maintained following the spray-drying process.…”
mentioning
confidence: 99%
“…Notwithstanding this, temperature of the outlet air is thought to be the most important factor. Daeman and Stege [8], and Kim & Bhowmik [12] showed that an increase of an inlet air temperature by 10 8C was equivalent to an increase of outlet air temperature by only 2.4 8C for L. delbrueckii subsp. bulgaricus, and by 1.8 8C for Streptococcus thermophilus (S. thermophilus).…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Daemen and Stege [8] suggest that inlet air temperature affected the destruction of cells and enzymes insignificantly. Kim and Bhowmik [12] found that a reduction of S. thermophilus population by a logarithmic cycle necessitated an increase of inlet air temperature by 66.6 8C, and of L. delbrueckii subsp. bulgaricus population by 43.9 8C.…”
Section: Introductionmentioning
confidence: 99%
“…Linear regression analysis were carried out from linear section of the curves. Cmr may be expressed by analogy with thermal destruction of microorganisms based upon a first order reaction rate (Kim and Bhowmik, 1990): dX = -cmrx or in integrated form: ln(X ) = ln(X0) -Cmr t dt where:…”
Section: Microorganismsmentioning
confidence: 99%